Social Atmospherics, Affective Response, and Behavioral Intention Associated With Esports Events - Jang, Wooyoung W.; Kim, Kyungyeol A.; Byon, Kevin K. (Frontiers in Psychology, 2020)
The purpose of this study was to conceptualize social atmospherics in the context of esports attendance and examine the relationship among social atmospherics, affective responses, and behavioral intention associated with esports events. Based on review literature, we conceptualized social atmospherics as five dimensions in esports events’ environments: social density, suitable behavior, similarity, cosplay, and cheering behavior. Notably, cosplay (i.e., a portmanteau of the words “costumes” and “play”) and cheering behavior factors adopted from extant social atmospherics served to capture the unique features associated with esports events. Via an online survey, data were collected (n = 372) from esports fans who have experienced attending esports events. The data set was split into half, so the first data set (n = 189) was used to examine the psychometric properties of the measurement model. The second data set (n = 184) was employed to test the hypothesized model. The initial model fit was not shown to be acceptable. The model fit was re-estimated using the second data set after dropping four items that showed low factor loadings. As a result, the model fit for the revised model was acceptable. The results via structural equation modeling indicated that cheering behavior, similarity, cosplay, and social density positively and significantly influenced affective responses and behavioral intention. However, there was no significant relationship between suitable behavior and affective responses. In terms of theoretical contributions, we tested a five-factor model of social atmospherics associated with esports events and its effect on behavioral intention through affective responses. The findings in this study extend the sportscape model (Wakefield & Sloan, 1995) by incorporating the mediating effect of affective responses and expand the utility of the SOR framework as a viable theory that can explain esports consumption behavior.